OP0308 Identifying Target Molecules Mediating Pain Processing in Osteoarthritis: Assessing TRPV1, TRPA1 and TRPM8 Expression in Joint Tissue. (23rd January 2014) - Kuttapitiya, A.; Davis, A.; Hing, C.; Dennis, J.; Sofat, N.
Abstract : Background: Osteoarthritis (OA) is the most common form of arthritis worldwide and is a leading cause of chronic pain and disability in adults aged over 60 years. In an aging population the number of individuals with symptomatic OA is set to rise, placing a higher burden on healthcare. Although it is common, there are currently no treatments that delay or halt the progression of OA. Pain is one of the major symptoms of OA and its management is an important factor to consider in the treatment of this condition. Despite the availability of analgesics, e.g. non-steroidal anti-inflammatory drugs (NSAIDs) and opioids, most agents do not control symptoms. Objectives: We sought to evaluate specific pain processing molecules of the TRP gene family, since these ion channels are implicated in mediating pain processing. Although TRPV1 channels are known to be expressed around cutaneous nerves, the expression of TRP members by human OA human bone and cartilage is not known. In this study, we investigated the expression of TRP channels VRI, A1 and M8 at the RNA and protein level from OA and normal controls. Methods: Joint tissue was obtained from participants undergoing total knee replacement surgery at St George's Hospital with full informed consent. Total RNA was extracted from the tissue with an on-column DNase digestion step using the RNeasy Micro Kit (Qiagen). RNA was reverse-transcribed using SuperScript II (Invitrogen). Endpoint PCR was performed using Platinum Taq (Invitrogen). PCR products were electrophoresed on a 2% agarose gel and visualized by SafeView nucleic acid stain (NBS Biologicals) on a transilluminator. Primers were designed and validated for TRPV1, TRPA1 and TRPM8 with beta actin as control. Relative gene expression in tissue was quantified using densitometry. Protein expression in joint tissue was evaluated by immunohistochemistry using a primary anti-TRPV1 antibody followed by horseradish peroxidase secondary antibody. Results: TRPA1 and TRPM8 were not expressed in OA bone and cartilage. In contrast, TRPV1 was expressed in cartilage and throughout bone taken from TKR surgery (14 regions from 7 participants). Amplicons corresponding to a portion of each gene were also detected in positive control tissue comprising of human brain in each experiment. We then went on to evaluate TRPV1 expression at the osteochondral junction in cartilage, since this area is known to be modified in OA. We found increased TRPV1 expression in cartilage in the pericellular region of chondrocytes in samples of OA tissue analysed. Conclusions: It is evident that TRPV1 is over-expressed in OA bone and cartilage, suggesting its involvement in pain mediation and further highlighting it as a candidate for pain treatment. Since the known function of TRPV1 includes detection and regulation of body temperature and sensation of heat and pain, or nociception, further evaluation of the site and time course of ion channel expression such as TRPV1 in OA tissue may help develop targeted therapies to manage pain in osteoarthritis. Acknowledgements: We thank the Rosetrees' Trust and The Wellcome Trust for funding. Disclosure of Interest: None Declared